Analisis Pemahaman Masyarakat Terhadap Kewajiban Zakat di Kecamatan Giligenting: Gambaran Pemahaman Masyarakat Terhadap Kewajiban Zakat di Giligenting - Kutrin Nadha Ma'arifah Putri (JURNAL EKONOMI, MANAJEMEN, BISNIS, DAN SOSIAL (EMBISS), 2021)
This study aims to find out how the community’s understanding of the obligation to pay zakat in Giligenting sub-district is, the extent to which efforts are being made to understand the obligation to pay zakat. This study uses qualitative data which aims to analyze the condition of the Giligenting community towards their obligation to pay zakat. Based on the results of the study, it shows that many people do not fully understand the meaning and purpose of zakat, what they understand is that zakat is only an order that must be carried out in the month of Ramadan, even though there are other zakat that must be implemented. Without them knowing, zakat is a problem that can release Muslims from poverty and a means of cleaning wealth from all kinds of selfishness.